2019
DOI: 10.21037/atm.2019.07.27
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic therapy of obesity: mechanisms of action and cardiometabolic effects

Abstract: Obesity is a chronic, relapsing, multifactorial disease, which has become a serious threat to public health globally, as the worldwide prevalence of obesity increases exponentially over time. It has been well established that obesity is associated with multiple adverse cardiometabolic effects. Although lifestyle changes are the first line of therapy for obesity, these are often insufficient in attaining weight loss goals.Orlistat, phentermine/topiramate, lorcaserin, naltrexone/bupropion, and liraglutide are ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 46 publications
(51 reference statements)
0
25
0
1
Order By: Relevance
“…Several compounds such as phentermine/topiramate, lorcaserin, naltrexone/bupropion and liraglutide, have been approved by the United States Food and Drug Administration to treat obesity. 2) The norepinephrine transporter inhibitor phentermine suppresses appetite by activating hypothalamic proopiomelanocortin arcuate nucleus neurons. Topiramate is an antiepileptic drug that also suppresses appetite by modulating activity of voltage-gated ion channels.…”
Section: Introductionmentioning
confidence: 99%
“…Several compounds such as phentermine/topiramate, lorcaserin, naltrexone/bupropion and liraglutide, have been approved by the United States Food and Drug Administration to treat obesity. 2) The norepinephrine transporter inhibitor phentermine suppresses appetite by activating hypothalamic proopiomelanocortin arcuate nucleus neurons. Topiramate is an antiepileptic drug that also suppresses appetite by modulating activity of voltage-gated ion channels.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence suggests that fecal microbiota transplantation (FMT) is a valuable and promising therapeutic option for diabetes and obesity disorders [ 131 ]. FMT showed beneficial effects by attenuating the pancreatic islet β-cell destruction and improving the insulin resistance in T2D patients [ 131 , 132 ], as well as reducing the low-grade chronic inflammation caused by a microbiota imbalance [ 131 ]. Moreover, a recent study by Who et al showed that altered gut microbiota mediates some of the antidiabetic effects of metformin, a drug widely used in T2D that inhibits complex I and enhances the ADP:ATP ratio, thereby activating liver AMPK to slow liver gluconeogenesis [ 133 ].…”
Section: Microbiota and Mitochondria: Potential Therapeutic Stratementioning
confidence: 99%
“…The most effective treatment for obesity prevention is dietary control and physical exercise-based therapies combined with pharmacological therapies, as well as bariatric surgery, but different lifestyles do not allow most people access to proper obesity therapy [7,8]. In contrast, many pharmacological therapies are available for obesity treatment, but their outcome is very limited and can involve many side effects [9]. Therefore, controlling obesity, a major cause of inflammation and cancer, with natural products and herbs has become increasingly popular [10].…”
Section: Introductionmentioning
confidence: 99%